KAJIAN PEMANFAATAN LAHAN RUANG TERBUKA HIJAU DI BAWAH JALUR TOL BECAKAYU, JATIBENING, KOTA BEKASI - Bahari, Wisnu; Zefri (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
The Becakayu Toll Road was built to reduce congestion and connect the capital city of DKI Jakarta with BekasiCity. The land under the Becakayu Toll road becomes empty, and then the community uses it for activities. Thisstudy aims to determine the pattern of public space utilization under the Becakayu toll road. The study wasconducted using a qualitative descriptive approach accompanied by interactive analysis including data reduction,data presentation, and conclusions. The existing condition of the land under the Becakayu Toll road is relativelygood, but it needs to be considered again, especially the potential size of the existing location. The activities underthe Becakayu toll road include trade, housing and services. The number of cars parked carelessly, garbage that haspiled up and glassware that has been deliberately left to add to the impression of a slum